SUMBER HUKUM HINDU DALAM MANAWA DHARMASASTRA - Ida Ayu Aryani Kemenuh (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Hindu Law Sources are the basic references used in taking Hindu Law. The main points of Hindu teachings that are believed and used as a basic reference are in the Book of Manawa Dharmasastra. The source of Hindu law can be reviewed in terms of history, sociology, philosophy, and formality. Based on Manawa Dharmaçastra, II. 6 sources of Hindu law are in Sruti, Smrti, Sila, Procedure and Atmanastuti. When compared with the form of state legislation, Sruti has similarities with the Basic Law. Sruti as the source or origin of other provisions. Smerti which contains regulations, guidelines for implementation, and teachings based on sruti, can be likened to Law. Precepts are teachings about the behavior of civilized people or legal principles recognized by the nation. The event is a custom that lives in the community. Atmanastuti is a sense of satisfaction in each individual who is a measure of every human effort. Efforts to Obey Hindu Law can be done by carrying out two obligations, namely the Dharma Religion and the State Dharma. The Dharma Religion is the obligation of the people to carry out religious teachings correctly. State Dharma is the obligation of religious people to be citizens, serve, and support all government regulations.Keyword: Hindu Legal Resources and Manawa Dharmasastra